Production of high-purity zinc single crystals by vertical directed crystallization method - Shcherban, A.P.; Kovtun, G.P.; Solopikhin, D.A.; Gorbenko, Yu.V.; Rudycheva, T.Yu.; Malykhin, D.G.; Kolodiy, I.V.; Virych, V.D. (Вопросы атомной науки и техники, 2020)
A seedless process has been developed to produce high-purity Zn single crystals by the method of vertical directed crystallization from a melt. The output of a single crystal structure is from 60 to 80%. Crystals with different growth directions were obtained: [1015] and [0002]. The deviation angles of the growth direction plane relative to the normal to the axis of the sample are 0.5…6°. Microhardness, crystalline perfection of single crystals and microstructure have been determined. The impurity composition of the start and end parts of single crystals produced from initial grades of zinc of various purities was studied. The developed process can be used to grow low-melting metals, such as Cd, Pb, Te, In, Bi, Sn, etc. Розроблено беззатравочний процес отримання високочистих монокристалів Zn методом вертикальної направленої кристалізації (ВНК) із розплаву. Вихід монокристалічної структури становить від 60 до 80%. Отримано кристали з різними напрямками зростання: [1015] і [0002]. Кути відхилення напрямку росту відносно осі стержнів складають 0,5…6°. Визначені мікротвердість, кристалічна досконалість монокристалів і мікроструктура. Досліджено домішковий склад початкової і кінцевої частин монокристалів, отриманих з вихідних марок цинку різної чистоти. Розроблений процес може бути використаний для вирощування легкоплавких металів, таких як Cd, Pb, Te, In, Bi, Sn і ін. Разработан беззатравочный процесс получения высокочистых монокристаллов Zn методом вертикальной направленной кристаллизации (ВНК) из расплава. Выход монокристаллической структуры составляет от 60 до 80%. Получены кристаллы с различными направлениями роста: [1015] и [0002]. Углы отклонения плоскости направления роста относительно нормали к оси образца составляют 0,5…6°. Определены микротвердость, кристаллическое совершенство монокристаллов и микроструктура. Исследован примесный состав начальной и конечной частей монокристаллов, полученных из исходных марок цинка различной чистоты. Разработанный процесс может быть использован для выращивания легкоплавких металлов, таких как Cd, Pb, Te, In, Bi, Sn и др.